Phenotypic and molecular characterization of cefotaximases, temoniera, and sulfhydryl variable β-lactamases in Pseudomonas and Acinetobacter isolates in an Indian tertiary health-care center - Sana Jamali; Mohammed Shahid; Farrukh Sobia; Anuradha Singh; Haris M Khan (Wolters Kluwer Medknow Publications, 2017)
Background: Cefotaximases (CTX-M), temoniera (TEM), and sulfhydryl variable (SHV) constitute a rapidly growing cluster of enzymes that have disseminated geographically. They are spreading to species other than Enterobacteriaceae and might be responsible for the presence of blaCTX-M,blaTEM, and blaSHVgenes in Pseudomonas and Acinetobacter spp. The present study was designed to characterize CTX-M, TEM, and SHV phenotypically and genotypically in Pseudomonas and Acinetobacter spp. Materials and Methods: A total of 90 isolates (73 Pseudomonas and 17 Acinetobacter spp.), resistant to any of the third-generation cephalosporins, were randomly selected from clinical samples. Results: Of 90 isolates, 64 (71.11%) were tested positive for extended-spectrum β-lactamase (ESBL) production. Among phenotypically tested ESBL producers, forty isolates were randomly selected for molecular characterization. The prevalence of CTX-M, TEM, and SHV was found to be 57.5%, 15%, and 75%, respectively. Multiplex polymerase chain reaction assay categorized blaCTX-Mgenes into Groups 1 and 26 where Group 1 was present in only 5 isolates and Group 25 was present in rest of the 18 isolates. Conclusion: This is among the premier systemic reports from India documenting phenotypic and molecular characterization of CTX-M, TEM, and SHV β-lactamases in Pseudomonas and Acinetobacter spp. With judicious use of antibiotics and strict infection control procedures, it may be possible to limit the effects of these newer β-lactamases.